Chemical-technological features of Malus sieversii clones in the Main Botanical Garden conditions (Experimental biology, 2018)
In this article the date of biochemical and technological quality features of fruits of Malus sieversii clones is given. M. sieversii differs by high intraspecific diversity in spread area and its fruit biochemical composition. Chemical and technological evaluation, which will be conducted for the first time using new clones of the Dzhungar population, are relevant. The aim of our work was the investigation of biochemical and technological quality features of fruit of M. sieversii clones and the selection of the most valuable cultivars for their processing and use in breeding. During our investigation 10clones of M. sieversii selected from different populations of the Dzungarian Alatau were engaged. To study the chemical composition of fruit the generally accepted methods were used. The percentage of dry matter, sugar, organic acids, water-soluble pectin, leucoanthocyanins and P-active substances was determined. The analysis was carried out during the period of 2012 till 2015. Fruits of the researched clones of M. sieversii in most cases were small and characterized by a higher acidity, from 1.11 to 1.73 %. Low content of acids was found in 2 clones. Among the M. sieversii clones possessing a high sugar-acid index, only 1 clone was outstanding. Among 10 clones of M. sieversii 4 of them were outstanding by high sugar content, up to 14%. The leucoanthocyanins’ content of the researched clones was from 74 to 651 mg per 100 g. High content of P-active substances was found in 4 clones. Most of the researched clones of M. sieversii demonstrated a high level of water-soluble pectin; it was from 1.04 to 2.5%. A high level of dry substance in fruit of the researched plants was noted. As a result of biochemical and technological characteristics of clones of M. sieversii, we have determined cultivars containing a high level of nutrients and biological active substances. And it can be used as a valuable source in breeding and product processing.Key words: Malus sieversii clones, chemical composition, biological active substances, apple fruit.